Antibacterial stewardship practices in South Africa during the COVID-19 era: A retrospective review - Spinickum, Logan Jade (University of the Witwatersrand, Johannesburg, 2024)
Background: Several mechanisms may facilitate and steer the development of antibiotic resistance patterns. The most prominent driver associated with antibiotic resistance has been indicated as inappropriate use or consumption of antibiotics. The sudden emergence of Coronavirus Disease 2019 (COVID-2019) changed the conventional practices related to drug utilisation through the repurposing of antibiotics. Despite the implementation of antibiotic stewardship programs, the pressure that COVID-19 placed on healthcare systems resulted in poor prescribing and antibiotic review practices, potentially exacerbating antibiotic resistance. Moreover, the public health sector faces various challenges that make it difficult to consistently assess and quantify antibiotic usage; while providing quality review, feedback, and intervention, especially in low- and-middle-income countries like South Africa. As a result, there is a paucity of information concerning antibiotic utilisation in the public healthcare sector, even following the emergence of the COVID-19 pandemic. It is essential to determine the extent of antibiotic use to improve antibiotic utilisation, patient outcomes and stimulate viable policies and initiatives to strengthen public healthcare drug surveillance amidst the challenges of increased infectious diseases, resistance, and health personnel shortages. Aim of study: The aims of the study were to determine, analyse and compare antibiotic consumption amongst intensive care unit (ICU) patients admitted in a Gauteng public hospital during the pre-COVID-19 era and commencement of the COVID-19 era. Methodology: A retrospective cross-sectional data analysis of 335 medical files of ICU patients hospitalised in a Gauteng Provincial Tertiary Hospital (GPTH) between January 2017 and December 2021. Descriptive statistics were used to examine patient characteristics and antibiotic prescribing variables. Results: The study found that the more frequently prescribed antibiotics were amoxicillin/clavulanate (pre-pandemic = 31.99%; COVID-19 = 38.43%), followed by ceftriaxone (pre-pandemic = 15.44%; COVID-19 = 14.55%), piperacillin/tazobactam (pre-pandemic = 11.40%; COVID- 19 = 8.58%) and azithromycin (pre-pandemic = 7.73%; COVID-19 = 19.78%). Common bacterial pathogens detected in both periods included Acinetobacter baumannii (pre-pandemic = 29.2%; COVID-19 = 20.9%), Enterobacter cloacae (pre-pandemic = 10.4%;COVID-19 = 14.0%), Escherichia coli (pre-pandemic = 22.9%; COVID-19 = 25.6%), and Klebsiella pneumoniae (pre-pandemic = 25.0%; COVID-19 = 18.6%). Resistance was predominantly observed in ciprofloxacin (pre-pandemic = 11.4%; COVID-19 = 12.9%), piperacillin/tazobactam (pre-pandemic = 12.7%; COVID-19 = 0.1%), cefotaxime (pre-pandemic = 13.2%; COVID-19 = 14.7%), and cefepime (pre-pandemic = 12.7%; COVID-19 = 11.2). Resistance to commonly prescribed antibiotics observed a decrease trend moving from the pre-pandemic period into the COVID-19 pandemic. Conclusion: The macrolide and penicillin (in combination with beta-lactamase inhibitor(s)), classes demonstrated an increase in prescribing and use across the pre-pandemic period transitioning into the COVID-19 pandemic. While overall resistance observed a decline moving into the COVID-19 pandemic. However, “Watch” category antibiotic resistance increased slightly. An increase in prescribing and use of macrolides coupled with an increase in “Watch” category antibiotic resistance, highlights the need for improved antibiotic stewardship programs in public healthcare and pathogen-directed prescribing, to combat inappropriate and unnecessary use of antibiotics.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Pharmacy (MPharm) to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg 2024
Keywords: Antibiotic use; Antibiotic prescribing; AwaRe antibiotics; COVID-19; PDD; Gauteng; Tertiary hospital; UCTD; SDG-3: Good health and well-being